Experimental identification of optimized process parameters for FSW of AZ91C Mg alloy using quadratic regression models - Satheesh, Chidambaram (Strojniški vestnik, 2020)
This experimental work aims to devise and establish quadratic regression equations, including various input criteria of a friction stir welding (FSW) technique to predict and determine the responses during the fabrication of AZ91C Mg alloy joints. The input process parameters taken into consideration include the traversing speed of the tool, the speed of rotation of the tool, its pin profile (geometry) and the axial force. A five-level, 4 four-factor composite design (of central nature) was applied, and response surface methodology (RSM) was used to formulate quadratic regression models, to develop 3D response surface charts, and to anticipate the responses for various mechanical properties. The generated quadratic mathematical model was tested and validated using the technique of analysis of variance. Validation experimental trial results outlined in the form of scatter diagrams revealed precedented coincidence with that of the generated models. The AZ91C Mg alloy joints obtained using the tool having taper cylindrical pin geometry employed at 1045 rpm, 1.5 mm/s traversing speed, under the exertion of an axial load of 4.87 kN was found to exhibit improved mechanical properties.
Keywords: aksialna sila; axial force; AZ91C Mg alloy; friction stir welding; geometrija čepa; kvadratni regresijski model; magnezijeva zlitina AZ91C; podajalna hitrost orodja; porušitvena natezna trdnost; quadratic regression model; tool pin geometry; tool rotational speed; tool traversing speed; ultimate tensile strength; varjenje z gnetenjem; vrtilna hitrost orodja